Attempt to standardize rainwater retention by green infrastructure - Dąbrowski, Wojciech; McGarity, Arthur (Instal, 2022)
We present the primary objectives in evaluating the potential for green rainwater retention. Next, we discuss the causes of undersizing rainwater and combined sewerage systems that makes green retention desirable in urban areas. We find that the primary reason for undersizing is the difficulties in developing correct guidelines for the required rainwater retention standards based solely on the dimensions and purposes of buildings. The location of buildings in relation to the sewerage network, flood risk and groundwater infiltration are determined to be the most important factors for selecting best green infrastructure types and the required rainwater retention volume. Finally, we propose further development of optimization models for green retention as a necessary next step towards progress in the field of green retention
Keywords: green infrastructure; sewerage systems; storm water; retention